- #1

Northbysouth

- 249

- 2

## Homework Statement

The Initial value problem:

y' - (3/t)y = 0

y(1) = -10

Has the solution:

I have attached an image of the question

## Homework Equations

## The Attempt at a Solution

Firstly I found the integrating factor:

u(t) = e

^{∫-3/t dt}

u(t) = -3/t

I plugged this back into the original equation:

(-3/t)y' + (9/t

^{2}y = 0

∫[-(3/t)y]' dt = ∫ 0 dt

(-3/t)y = C

y = -Ct/3

But I don't understand where I go from here. The possible answers all include t

^{3}and I don't understand where that has come from. What step did I miss?